Family Structure and Child Outcomes in the United States and Sweden - Anders Björklund; Donna K. Ginther; Marianne Sundström (Institute for the Study of Labor (IZA), 2004)
It is well known that children reared in non-intact families on average have less favorable educational outcomes than children reared in two-parent families. Evidence from the United States and Sweden indicates that living in a non-intact family is correlated with lower educational attainment. In this paper we compare the relationships between family structure and children?s outcomes in terms of educational attainment and earnings using data from Sweden and the United States. Comparing the United States and Sweden is interesting because both family structure and public policy environments in the two countries differ significantly. Family structure could potentially have a less negative effect in Sweden than in the United States because of the extensive social safety net provided by that country. We find, however, the associations between family structure and children?s outcomes to be remarkably similar in the United States and Sweden even though the policy and social environments differ between the two countries; living in a non-intact family is negatively related to child outcomes. This relationship is weakened when we control for other family characteristics, such as time lived with full and half siblings. In addition, when we use siblingdifference models to take account of unobserved family characteristics, the relationship is no longer statistically significant. Taken together, our results suggest that the true effect of family structure is more complex than the biological relationship of parents to children in both Sweden and the United States.
Keywords: I21; J12; J1; 330; family structure; parental separation; child welfare; educational attainment; Bildungsniveau; Bildungsertrag; Kinder; Familiensoziologie; Ehe; Schätzung; Vergleich; Vereinigte Staaten; Schweden